2022
DOI: 10.1155/2022/1258480
|View full text |Cite
|
Sign up to set email alerts
|

A Pyroptosis-Related Gene Signature to Predict Patients’ Prognosis and Immune Landscape in Liver Hepatocellular Carcinoma

Abstract: Background. Liver hepatocellular carcinoma (LIHC) is a malignance with high incidence and recurrence. Pyroptosis is a programed cell death pattern which both activates the effective immune response and causes cell damage. However, their potential applications of pyroptosis-related genes (PRGs) in the prognostic evaluation and immunotherapy of LIHC are still rarely discussed. Methods. Comprehensive bioinformatics analyses based on TCGA-LIHC dataset were performed in the current study. Results. A total of 33 PRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Besides, we constructed a novel multigene predictive model for HCC patients and validated the model genes' expression differences through several different analyses. Recently, some similar studies about different PRG research in HCC subtype identification [40][41][42][43][44][45][46] and predictive model construction [40][41][42][43][44][45][46][47][48][49] have been published. However, in all the previous subtype identification studies, the cluster analyses were conducted only in one cohort while we also tested in a validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we constructed a novel multigene predictive model for HCC patients and validated the model genes' expression differences through several different analyses. Recently, some similar studies about different PRG research in HCC subtype identification [40][41][42][43][44][45][46] and predictive model construction [40][41][42][43][44][45][46][47][48][49] have been published. However, in all the previous subtype identification studies, the cluster analyses were conducted only in one cohort while we also tested in a validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Some related studies have been on pyroptosis-related gene signatures in HCC, which proved that PRGs played important roles in predicting the prognosis of HCC [ 6 – 8 ]. Unlike these studies, we firstly added mutation data analysis of PRGs, and the ICGC-LIRI-JP dataset to verify the validity of the model.…”
Section: Discussionmentioning
confidence: 99%
“…The results of qRT-PCR suggested that BAK1, BAX, CHMP2A, GSDME, IL1A, TP53, TP63, GPX4, PRKACA and SCAF11 were highly expressed in HCC tissues. Some related studies have been on pyroptosis-related gene signatures in HCC, which proved that PRGs played important roles in predicting the prognosis of HCC [6][7][8]. Unlike these studies, we firstly added mutation data analysis of PRGs, and the ICGC-LIRI-JP dataset to verify the validity of the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copy number amplification was detected while its expression was significantly differentiated among HCC and the neighboring healthy tissue. Concerning the predictive value of NLRP3, the highest expression of NLRP3 was associated with poor OS [96].…”
Section: The Nlrp3 As Biomarkermentioning
confidence: 97%